Religious Affiliations and Clinical Outcomes in Korean Patients With Acute Myocardial Infarction - Oh, Seok; Kim, Ju Han; Cho, Kyung Hoon; Kim, Min Chul; Sim, Doo Sun; Hong, Young Joon; Ahn, Youngkeun; Jeong, Myung Ho (Frontiers in Cardiovascular Medicine, 2022)
Objective Although religion is expected to have a direct or indirect effect on various aspects of human life, information on the association between religion and acute myocardial infarction (AMI) is inadequate. Hence, in this study, we aimed to investigate the clinical effect of religion on clinical outcomes in patients with AMI. Methods A total of 2,348 patients with AMI who were treated by percutaneous coronary intervention (PCI) were enrolled in the study, and they were categorized into two groups depending on their religious belief: religious and non-religious groups. The characteristics and clinical outcomes of both groups were compared. Results Compared with the religious group, the non-religious group was younger, included mostly men, was more likely to smoke, and was more likely to be diagnosed with ST-segment elevation myocardial infarction. However, the non-religious group was less likely to have a history of hypertension and tended to receive PCI more quickly with shorter door-to-balloon time. Regarding 1-year clinical outcomes, no differences were found between the two groups. Conclusion Despite a growing body of evidence that religious activities have positive effects on human physical health, our results showed a lack of significant differences in 1-year clinical outcomes in patients with AMI irrespective of their religious beliefs.